Survival of Persons with Down Syndrome in Italy - Rosano, Aldo (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
Down syndrome (DS) is a major cause of congenital malformation and disability. No updated data are available on life expectancy of persons with DS in Europe. We collected information on age, sex and area of birth of 3,217 persons with DS died from 1997 to 2009 in Italy. Survivals rates and mean survival time was calculated using a life tables calculated from cross sectional data. Some factors influencing the survival were also analysed using a semi-proportional hazard model. Survival rates of 91.4% at one year and 88.3% at ten years were found. Mean survival time at birth was 47.1 years (C.I. 95%: 46.5-47.7). There was 8-year significant difference in survival between north-central regions and southern regions. Male life expectancy was 46.9 years (C.I. 95%: 46.1-47.8), lower than females 47.3 years (C.I. 95%: 46.5-48.2) even though not statistically significant (p=0.23). Almost nine out ten children with DS now survive at least 10 years. Adequate educational and health service provisions needs to be made for them. The disadvantage of Down persons born in the Southern regions in terms of life expectancy is impressive. Quality of medical care provided in the South of Italy in the first months of life is the most likely determinant of the high mortality observed among persons with DS born in that area.